2023
DOI: 10.2147/opth.s403433
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection for Nonarteritic Central Retinal Artery Occlusion: Lessons from Acute Ischemic Stroke

Abstract: Nonarteritic central retinal artery occlusion (NA-CRAO) is a variant of acute ischemic stroke (AIS) and is a cause of sudden severe loss of vision. There are guidelines by the American Heart Association and the American Stroke Association for the care of CRAO patients. This review explores the basis of retinal neuroprotection for CRAO and its potential for improving the outcome of NA-CRAO. Recently, there have been significant advances in research into the use of neuroprotection to treat retinal diseases, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
(149 reference statements)
0
0
0
Order By: Relevance
“…PAM can simultaneously image anatomical, functional, molecular, flow dynamic, and metabolic contrasts in vivo [148]. PAM has been used for macular blood flow imaging in retina vaso-occlusive diseases [149]. Of interest is that PAM has been integrated with adaptive optics for highresolution retina imaging [150].…”
Section: Other Macular Imaging Techniquesmentioning
confidence: 99%
“…PAM can simultaneously image anatomical, functional, molecular, flow dynamic, and metabolic contrasts in vivo [148]. PAM has been used for macular blood flow imaging in retina vaso-occlusive diseases [149]. Of interest is that PAM has been integrated with adaptive optics for highresolution retina imaging [150].…”
Section: Other Macular Imaging Techniquesmentioning
confidence: 99%
“…Yet another review by Janská et al concluded, "It seems that the IVT efficacy and safety can be confirmed" [31]. Okonkwo et al made a case for neuroprotective strategies in patients with CRAO, and on the subject of IVT state "...intravenous (IV) thrombolysis (IV-tPA) in CRAO though controversial, could hold some promise for a category of patients who can have treatment early and perhaps suffer from incomplete arterial occlusion" [32]. A 2023 Cochrane review, which looked at six RCTs, totaling 223 participants with acute nonarteritic CRAO, could not provide a strong recommendation for IVT in CRAO [11].…”
Section: Literature Overviewmentioning
confidence: 99%
“…29 New trials are currently ongoing. 31 The lack of proven beneficial effect of thrombolysis to date supports the point of view from Hayreh, a prominent clinical scientist in ophthalmology and vascular diseases of the eye specifically. Based on studies showing e.g.…”
Section: Treatment Of Raomentioning
confidence: 90%
“…34 In contrast, neuroprotective treatments for RAO have received less attention. This new approach to treatment of RAO adopted from stroke was however very recently pointed out by Okonkwo et al 31 In their paper, they specifically highlighted the potential of developing neuroprotective therapies for RAO, further emphasized by the absence of effective revascularizing treatments.…”
Section: Treatment Of Raomentioning
confidence: 99%
See 1 more Smart Citation